2022
DOI: 10.4149/neo_2021_210607n761
|View full text |Cite
|
Sign up to set email alerts
|

NCAPH regulates gastric cancer progression through DNA damage response

Abstract: Gastric cancer (GC) is one of the most common devastating and deadly malignancies of the gastrointestinal tract in the world. GLOBOCAN data analysis showed that GC accounted for approximately 1,033,000 new cases of cancer and 78,200 deaths in 2018. Nonstructural maintenance of chromosomes (non-SMC) condensin I complex subunit H (NCAPH) is a regulatory subunit that encodes the non-SMC condensin I complex. Previous studies have demonstrated that NCAPH is highly expressed in multiple cancers. This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…Therefore, understanding the mechanism of COAD drug resistance is essential for improving patient survival. In recent years, abnormally expressed NCAPH has been found in breast cancer, endometrial cancer, NSCLC, and gastric cancer [24,30–32]. In this study, we found high expression of NCAPH in COAD, which was in line with the findings of Yin L et al [26].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, understanding the mechanism of COAD drug resistance is essential for improving patient survival. In recent years, abnormally expressed NCAPH has been found in breast cancer, endometrial cancer, NSCLC, and gastric cancer [24,30–32]. In this study, we found high expression of NCAPH in COAD, which was in line with the findings of Yin L et al [26].…”
Section: Discussionsupporting
confidence: 92%
“…In the last ve years, high levels of NCAPH expression have been associated with the pathogenesis and prognosis of several tumor types (32)(33)(34)(35)(36)(37)(38)(39)(40), including hepatocarcinoma (41), lung tumors (42)(43)(44), melanoma (45), endometrial cancer(46) and hormone-dependent BC (22,47). Here, we demonstrate that NCAPH participates in the pathogenesis of BC in vivo and in vitro.…”
mentioning
confidence: 64%
“…[81][82][83][84][85][86] with worse outcome are thought to have higher genomic instability, alterations to P53 19 and overexpression of genes that regulate mitosis. 20 In the last 5 years, high levels of NCAPH expression have been associated with the pathogenesis and prognosis of several tumour types, 81,82,84,[86][87][88][89][90][91] including hepatocarcinoma, 92 lung tumours, 93-95 melanoma 96 and endometrial cancer. 83 During the development of this project, two studies on NCAPH in breast cancer were published.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 5 years, high levels of NCAPH expression have been associated with the pathogenesis and prognosis of several tumour types, 81 , 82 , 84 , 86 , 87 , 88 , 89 , 90 , 91 including hepatocarcinoma, 92 lung tumours, 93 , 94 , 95 melanoma 96 and endometrial cancer. 83 During the development of this project, two studies on NCAPH in breast cancer were published.…”
Section: Discussionmentioning
confidence: 99%